Authoring tool for creating tangible interaction-based educational activities - Artola, Verónica (2015)
This paper presents the design of an authoring tool for creating educational activities based on tangible interaction. First, background information is presented in relation to tangible interaction and its possibilities for the educational context. Also, the concept of authoring tool is reviewed, and a number of desirable features for authoring tools oriented to the educational context are listed. Finally, TIES (Tangible Interaction in Educational Scenario) is described, which is the authoring tool we designed and upon which this paper is focused. The reasons why this is a necessary tool are discussed, and some conclusions and future lines of work are presented.